Possibilities and Limitations of Participative Governance: Public Participation in Water Governance in Finland and Sweden - Eilola, Sanna-Maarit (My University, 2011)
The aim of this study is to analyse citizen participation in small water restorations. Citizens are viewed as stakeholders in certain geographic area, that is, landowners near stream waters. Citizen participation is especially important in small water restorations for two main reasons. First, a permit is needed from landowners for restorations to be at all possible. Second, citizens are needed for volunteer work. The main research question is: What are the possibilities and limitations of participative governance? The following additional questions clarify the main question: 1) What is participative governance? What does it signify concerning small water restorations? 2) Water governance both in Finland and Sweden. What are the laws, officials and procedures behind stream restorations? 3) The key elements in encouraging people to participate in small water restorations, both in Finland and Sweden. Are there differences between Finnish and Swedish landowner’s views? The theoretical contribution of the study concentrates on the different aspects of citizen participation. Citizen participation can be defined as a synonym for citizen power. The citizens should have real power needed to affect the outcome of different participation processes. Furthermore, water governance and the general idea of small water restorations are discussed. Small water refers to for instance forest streams, pools and springs. Stream restoration can be defined as returning to the natural or undisturbed state of the water ecosystem. The new European Water Policy influences in the background of small water restorations. Its goal is to get polluted waters clean again, and to ensure clean waters are kept clean. The study is comparative in nature. The cases are analyzed using a quantitative approach. The comparison is based on a questionnaire made for the study, realized both in Finland and Sweden to grasp on people’s attitudes towards small water restorations. The material is based on literature, websites and other publications, such as magazines, chosen within the framework of the study. Main findings can be summarized as follows. First, to increase willingness to participate citizens need to be offered with a sufficient amount of information. Second, the willingness to participate is limited because of attitudes concerning for instance small waters and their importance. Third, it is possible to increase the willingness to participate by developing better opportunities to cooperate. As a conclusion, it can be said that on one hand, the officials have not succeeded so far in the goal of getting citizens to participate in restorations and to work together in collaboration. On the other hand, despite the fact that the public is not participating in restorations of small waters in a sufficient extent, the citizens are nevertheless more aware and worried about the state of small waters. Perhaps in the future people would like to participate more in the decisions that have a direct effect on them. The challenge is to transform this desire in to actual participation.
Keywords: citizen participation; water governance; stream restorations; the European Union; The new European Water Policy; fi=Julkisjohtaminen: European Civil Servants - kansainvälisen hallinnon ohjelma|en=Public Management: European Civil Servants|